TTTI Extension Centre Pune, Past-Present-Future - Mahashabde, R. S. (Journal of Engineering Education Transformations, 1998)
When Govt. of India established four Technical Teachers' Training Institutes in the country, Govt. of Maharashtra decided to establish its own Technical Teachers' Training College (ITTC) in 1965. This was established at Karad and subsequently it was shifted to Pune in 1971.